THE DILEMMA OF DHARMA IN THE GĪTĀ: Religious Constraints on Moral Duty - Sequeira, Cinderella (Journal of Dharma, 2013)
The Bhagavad Gītā demands adherence to its teachings particularly on dharma. One’s svadharma is prescribed as one’s sādhāraṇa dharma or one’s varṇa-āśrama dharma with the latter taking precedence over the former. Performance of dharma with desirelessness for the fruit of the action or niṣkāma karma leads one to attain the state of sthitaprajña. Adherence to one’s dharma promises Mokṣa to a sthitaprajña and Loksamgraha to the society. This paper approaches dharma in the Gītā with a critical eye on its obligatory, exclusive and hierarchical perspective on dharma. It questions its goal of Loksamgraha and explores the hereditary limits it places on individual knowledge and choice.